Estimation on Pressure and Velocity Parameter in the Fuel Handling Pneumatic Design of RDE. (March 2020) - Dibyo, Sukmanto; Setiadipura, Topan; Pancoko, Marliyadi
Abstract: The RDE is small size of High Temperature Gas-Cooled Reactor type. It's being designed that have a power of 10 MW thermal, which is intended to produce the electricity and heat utilization. The reactor uses helium gas as a system of coolant at the pressure of 3.0 MPa. The fuel pebble of spherical shape are transported by the pneumatic system in the pipes and recharged from the reactor core continuously without shut-down the reactor. During the process of transportation, the fuel pebble is lifted perpendicularly along the pipe into the reactor core. Therefore, fuel pebble transportation in the pneumatic system is an important effect to stability the fuel handling operation. This paper to estimate the fuel pebble velocity through a vertical pipe with respect to the pressure of pneumatic system in the design of RDE. The pneumatic vertical pipe has 23 m length, 65 mm inner diameter and fuel pebble of 60 mm diameter, weight of one fuel pebble is 200 gr and contains an uranium kernel coated in matrix graphite. The pneumatic system of carrier gas compressed as the conveying medium must be able to transport the fuel pebble through the pneumatic pipe one by one continuously, so that it could be loaded into the reactor core safely. In the pneumatic conveying, the general equation for the velocity of an object movement, drag force of flow and Bernoulli principle were used in the analysis. An initial velocity in range of 20 to 23 m/s was analysed, meanwhile, the fuel pebble discharged from the pneumatic pipe was determined at low velocity around of 0.1 to 5.0 m/s. In this case a collision at high velocity with the reactor core that causes pebble damage can be avoided. Result shows that the pneumatic transportation for the operational requirements of the fuel handling system when the carrier gas pressure in the range of 0.09 to 0.11 MPa higher than the reactor pressure system. In order to perfectly calculation in the future, it will consider the drag coefficient on the fuel pebble with a pipe wall.